Peran Media Pembelajaran Interaktif dalam Mendukung Perkembangan Peserta Didik Sekolah Dasar - Novita Dwy Khairunnisa; Seftian Wahyu Ningtias; Marvela Putri Angraeni; Disya Nabila Hana Mardiah (Prosiding Konferensi Ilmiah Dasar, 2026)
The rapid advancement of digital technology has significantly transformed education, particularly through the use of interactive learning media that enhance students' critical thinking skills. This study aims to systematically analyze the role of interactive learning media in improving critical thinking in mathematics learning at the elementary and secondary school levels. A Systematic Literature Review (SLR) was conducted by examining seven scientific articles on various interactive media, including e-modules, animated videos, TPACK-based online comics, GeoGebra, Google Slides, TPACK-based student worksheets (LKPD), metacognitive strategies, Android-based educational games, and Kodular-assisted e-modules. The review followed three stages: planning, implementation, and reporting. The findings reveal that these interactive media are generally valid, practical, and effective in fostering students' critical thinking skills. The study concludes that integrating interactive learning media into mathematics instruction can improve learning outcomes and promote higherorder thinking.